N6-Methyladenosine RNA Methylation Regulators Have Clinical Prognostic Values in Hepatocellular Carcinoma - Liu, Wei; Zhong, Cuiqing; Lv, Deguan; Tang, Mengjie; Xie, Feng (Frontiers in Genetics, 2020)
Although it is generally accepted that N6-methyladenosine (m6A) RNA methylation plays critical roles in tumorigenesis and progression, the values of m6A modification are less known in hepatocellular carcinoma. The major purpose of current studies is to investigate the role of m6A regulators in hepatocellular carcinoma and whether it can affect the prognosis of hepatocellular carcinoma. Here, we demonstrate that most of m6A regulators are highly expressed in hepatocellular carcinoma. Furthermore, we cluster hepatocellular carcinoma into two subgroups (cluster1/2) by applying consensus clustering to m6A regulators. Compared with the cluster 1 subgroup, the cluster 2 subgroup was significantly associated with higher pathological grade and survival. Based on these findings, we reveal a risk signature by using three m6A regulators which are not only an independent prognostic marker but also a predictor of the clinicopathological features in hepatocellular carcinoma. In conclusion, m6A regulators are crucial participants in the malignant progression of hepatocellular carcinoma and are the potentially useful target for prognosis